2010
DOI: 10.3892/or_00000822
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological evaluation including cytokeratin 13 and Ki-67 in the border between Lugol-stained and -unstained areas

Abstract: Abstract. Lugol's iodine staining (Lugol-staining) has been widely used to detect malignant changes in the cervix uteri and esophagus. However, pathological and histochemical changes in the border between Lugol-stained and -unstained areas in oral epithelial dysplastia and malignant lesions are not well understood. We examined the histological appearance of 20 cases of epithelial dysplasia surrounding squamous cell carcinoma using HE and PAS staining in the borders between Lugol-stained and -unstained areas. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 16 publications
1
18
0
5
Order By: Relevance
“…2e). These results reinforce previous findings, which confirmed that the loss of CK13 expression in dysplastic epithelium appears to follow the process of malignant transformation [11,13,[15][16][17].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…2e). These results reinforce previous findings, which confirmed that the loss of CK13 expression in dysplastic epithelium appears to follow the process of malignant transformation [11,13,[15][16][17].…”
Section: Discussionsupporting
confidence: 94%
“…Although the expression of cytokeratin 10 and 13 has been widely investigated in oral malignant and precancerous lesions [10][11][12][13][14][15][16][17][18], only one of these studies was conducted in actinic cheilitis [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][8][9][10][11][12][13][14] Regarding the disappearance of K13 in laryngeal squamous cell carcinomas (SCCs) with definite keratinization tendencies, masking or modification of K13 antigenic sites due to some dysfunction of the K13 gene has been suggested. 11 However, there has been no investigation on the K13 gene expression levels in the oral squamous epithelial lesions lacking the immunohistochemical expression of the K13 protein.…”
Section: Introductionmentioning
confidence: 99%
“…Yet these techniques are used for research purposes and are not clinically applicable. (Bourhis et al 1996 ;Remmerbach et al 2001;Maraki, Becker, and Boecking 2004;Maraki, Hengge, et al 2006;Maraki, Yalcinkaya, et al 2006;Yamazaki et al 2008 ;Nagamani et al 2010;Mohtasham et al 2010;OHTA et al 2010;Böcking et al 2011). In addition these methods are expensive and are not widely accessible and only expert clinicians can use them for early diagnosis.…”
Section: Cellular and Molecular Techniquesmentioning
confidence: 99%